2021
DOI: 10.1097/prs.0000000000008506
|View full text |Cite
|
Sign up to set email alerts
|

Direct-to-Implant Prepectoral Breast Reconstruction: Patient-Reported Outcomes

Abstract: Background: Direct-to-implant prepectoral breast reconstruction has recently experienced a resurgence in popularity because of its lower levels of postoperative pain and animation deformity. BREAST-Q, a well-validated patient-reported outcomes tool, was used to assess patient satisfaction and quality of life. The goal of this study was to assess patient-reported outcomes at 6-month and 1-year follow-up after direct-to-implant prepectoral breast reconstruction. Methods: Sixty-nine consented adult patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 36 publications
1
7
1
Order By: Relevance
“…In the current study, complications occurred in 29.7% of patients. This result was comparable with those of previously reported studies, 1,2,14,19,20 in which the range was reported as being 5.7%–30.3% of patients. Most published studies regarding an association of postoperative complications with NACT were conducted in subpectoral cases.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, complications occurred in 29.7% of patients. This result was comparable with those of previously reported studies, 1,2,14,19,20 in which the range was reported as being 5.7%–30.3% of patients. Most published studies regarding an association of postoperative complications with NACT were conducted in subpectoral cases.…”
Section: Discussionsupporting
confidence: 93%
“…Safran et al reported that the use of ADM in DTI breast reconstruction did not have significant effects on patient-reported outcomes. 30 However, Singla et al reported their experience of DTI without ADM, which showed higher complication rates than our report, 31 and the possibility of a lot of scarring reaction cannot be excluded because the surrounding tissue can be used to stabilize the implant position without ADM. For those reasons, many surgeons have performed the prepectoral DTI breast reconstruction with the ADM.…”
Section: Discussioncontrasting
confidence: 65%
“…A study of 69 patients undergoing single-stage, prepectoral direct to implant reconstruction noted no difference in BREAST-Q scores preoperatively and postoperatively at 6 and 12 months ( 41 ). A similar study showed similar BREAST-Q scores when comparing prepectoral to subpectoral direct-to-implant reconstruction in 64 patients with only sexual well-being being scored higher in the subpectoral implant cohort ( 42 ).…”
Section: Discussionmentioning
confidence: 99%